Implementation and impact of poverty alleviation programmes in Himachal Pradesh: a tribal and non-tribal comparative study - Dayal, Shiv; Thakur, Dalip S. (1999)
A large number of studies on the implementation and impact of poverty alleviation programmes either on the tribals or on the non-tribals have been conducted at the national and state level both by the government agencies as well as by the individual scholars. But so far a comparative study on the implementation and impact of poverty alleviation programme among the tribals and non-tribals has not been conducted in the state of Himachal Pradesh. This study being the first of its kind attempts to present a comparative picture of the implementation and impact of poverty alleviation programmes among the tribals and non-tribals in Himachal Pradesh. - Reproduced
Keywords: Poverty - India - Himachal Pradesh; Poverty